Digital Leadership: Its Influence on Driving Digital Policy Adoption in the Public Sector - b, irfan; Djabbari, Muhammad Hidayat; Herianto, Dedy; Yanto, Erwing; Faisal , Andi Fahri (Perkembangan Kajian Sosial, 2024)
This study examines the pivotal role of digital leadership in driving government transformation. By leveraging advanced data analytics, governments can formulate more predictive policies and anticipate future challenges. Digital services enhance efficiency, accessibility, and transparency, fostering trust in government institutions. However, successful digital transformation hinges on effective leadership. Digital leaders possess the skills to navigate complex digital environments, cultivate digital mindsets, and identify opportunities. This research explores the competencies required for digital leadership, including data analytics, strategic thinking, and the ability to inspire and motivate teams. Furthermore, it investigates the impact of digital leadership on policy adoption, service delivery, and organizational culture. Through a comprehensive literature review, this study contributes to the understanding of how digital leadership can accelerate government modernization and improve public service delivery.